Strategi Pemasaran dan Distribusi Dalam Ritel Besar Studi Kasus di CV Perindo Kota Gunungsitoli - Yarni Kasih Tafonao; Maria Magdalena Batee; Sophia Molinda Kakisina; Yupiter Mendrofa (Lembaga Pengembangan Kinerja Dosen, 2025)
The urgency of this research is increasingly felt considering the impact that can be caused if marketing and product distribution problems are not managed well. Failure in product marketing and distribution causes the product to not reach consumers at the right time and in good condition, so that consumers are dissatisfied and will not buy the product again. The type of research used is qualitative, with data collection techniques through interviews, observation and documentation. The data analysis technique used uses the Milles and Huberman model. The results of this research are a) CV. Perindo implements a marketing strategy by utilizing a combination of direct distribution through retail stores and e-commerce, as well as indirect distribution through wholesalers and retailers, which allows the company to expand the market while maintaining sales control, b) Success and failure of marketing at CV. Perindo is influenced by internal factors such as product quality and inventory management, as well as external factors such as economic conditions and market competition, which require the company to continuously adapt to market dynamics. and c) Digital technology plays a crucial role in increasing the efficiency of CV marketing and distribution. Perindo, where e-commerce expands consumer reach at lower costs, while data digitization helps companies make fast decisions and be responsive to market demand.CV. Perindo should develop digital technology in e-commerce and inventory, improve employee skills through training, and continue to monitor market dynamics and adjust marketing and distribution strategies to remain efficient, relevant and competitive in the local retail market.